Gain-of-function defects in toll-like receptor 8 shed light on the interface between immune system and bone marrow failure disorders - Bleesing, Jack (Frontiers in Immunology, 2022)
In this article, we will share lessons that patients with gain-of-function defects in Toll-like Receptor 8 (TLR8-GOF), can teach us about the Interface between bone marrow failure (BMF) disorders and Inborn Errors of Immunity (IEI), subsequently referred to as “Interface Disorders”. TLR8-GOF is a relatively young entity (from a discovery standpoint) that – through both similar and dissimilar disease characteristics, can increase our understanding of Interface Disorders, for example as it pertains to pathophysiology, genetic mechanism of disease, and – related - diagnostics and therapeutics From a genetics point of view, TLR8-GOF joins a growing list of (Interface) disorders that can cause disease both with germline and somatic (mosaic) genetic variants. This not only has repercussions for the diagnostic workup of these disorders, in as-much that routine genetic testing may miss somatic variants, but has therapeutic implications as well, for example with the approach to curative treatment, such as hematopoietic stem cell transplantation. Following an introduction and schematic rendering of the Interface, we will review salient features of TLR8-GOF, with the understanding that the phenotype of this new disorder likely is not written in stone yet. In keeping with the principle of “Form Follows Function”, we will discuss specific immunological biomarkers that can be measured in clinical laboratories and highlight key disease features that pertain to can be found in several Interface disorders. As can be seen from a schematic representation, the Interface provides opportunities for learning and collaboration with respect to shared diagnostics, but also the potential for drug repurposing and precision therapeutics. Ideally, collaboration also focuses on education and teaching, such that cross-fertilization and collaboration across these disciplines can create a framework for complementary research.